Regional perspectives on socio-technical transitions: Combining research insights from geography of innovation and transition studies - Hendrik Hansmeier; Knut Koschatzky; Andrea Zenker; Thomas Stahlecker (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
While societal challenges are global in nature, solving and addressing them usually tends to take place at smaller spatial scales. As place-specific technological, institutional and actor settings have a decisive influence on the direction, scope and speed of transformative dynamics, regions vary greatly in the generation and application of innovations required for socio-technical transitions. With a broader understanding of regional innovation systems (RIS), on the one hand, and spatial considerations in transition studies, on the other, geographic research has recently contributed to a better understanding of innovation-based structural and systemic change. At the same time, the research findings are still insufficiently linked with one another. We argue that recent theorizing on expanded regional innovation systems provides additional explanatory power in the context of sys-temic transitions by considering similar aspects, e.g. the role of experimentation and different modes of innovation, yet incorporating a more spatial perspective. Against this background, we show that innovation policies at the regional level seem to be particularly effective when they sup-port innovation dynamics aimed at sustainability through the inclusion of various actor groups and the attention to both the production and application side. Given the increasing spatial disparities in innovation dynamics, however, further research is needed on the opportunities and barriers of different regional settings for sustainability transitions.
Keywords: 330